The effects of anxiety and depression on asthma control and their association with strategies for coping with stress and social acceptance - CEYHAN, BERRİN (ELSEVIER MASSON, CORP OFF, 2020)
Aim. - Chronically ill patients may be preoccupied with health issues such as anxiety and depression that can heighten emotional difficulties, and previous studies have reported an association between asthma and depression and anxiety. The literature contains limited data about the relationship between negative psychological state and control in asthma patients. We aimed to evaluate psychiatric comorbidities such as anxiety and depression in addition to coping strategies in terms of stress management and social desirability in asthma patients, and sought to investigate their impact on asthma control. Study design and method. - A total of 88 adult asthma patients were included in the study. They underwent physical examination, as well as pulmonary function testing and an asthma control test: (ACT), and their body mass index (BMI) was determined. All participants completed the following questionnaires: the Hospital Anxiety and Depression Scale (HADS), the Coping Strategies with Stress Inventory-Short Form (COPE), and the Marlowe Crowne Social Desirability Scale-Short Form (MCSD). Results. - Anxiety was found in 55% and depression was found in 62% of asthmatic patients. Compared to men (32%), a significantly higher proportion of women (61%) had anxiety (A = 0.023). ACT scores were significantly lower for patients with anxiety and depression than for patients without [18 (15-21) vs. 19 (17-23), P= 0.028] and [18 (15-21) vs. 21 (17-23), P= 0.003, respectively]. Turning to religion and Planning were the leading coping strategies in all asthmatics. 41% of patients had controlled asthma while 59% had uncontrolled asthma. Seeking Social Support for Instrumental Reasons was more common in patients with uncontrolled asthma than in those with controlled asthma (A = 0.029). The coping strategies of Behavioral Disengagement (P= 0.02, P= 0.011, respectively) and Self-Accusation (P= 0.018 and P = 0.016, respectively) were more prevalent among patients with anxiety and depression, while nondepressive asthma patients most frequently used Positive Reinterpretation, Acceptance, Humor and Seeking of Emotional Social Support as ways of coping with stress compared to subjects with depression (P= 0.002, P= 0.034, P= 0.01, P= 0.006, respectively). There was no statistically significant difference between social desirability indexes for the controlled and uncontrolled asthma groups. Conclusions. - It is known that psychiatric disorders may affect the clinical course of asthma. This real-life study suggested the importance of assessing depression and anxiety symptoms in addition to strategies for coping with stress and achieving social approval to improve asthma control in clinical practice. Knowledge of the approach adopted by individuals to cope with stressful conditions may help in determining treatment targets and monitoring therapeutic efficacy. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: QUALITY-OF-LIFE; DISORDERS; STYLES; SYMPTOMS; DISEASE; ADULTS; WORSE